Political Leadership from the Bottom: A New Theoretical Model of Followership - Luong Mai Lam, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Different from many previous studies on leadership which focus on leadership within management science, this paper gives a fresh look by investigating the followership characteristics in the political approach. A new model adapted and renovated from Kelley (1992) on the followership model is applied to define the types of followers from a political perspective. The paper also used synthesis of the literature, observations, and survey data conducted by research centers such as the International Institute for Democracy and Electoral Assistance, TCdata360, and Freedom House. Empirical evidence of three typical examples indicates that sheep followers are the major group in highly authoritarian leadership in China, while the archetype followership in Norway can receive a full democratic leadership style. In a more complicated case, the outsider type in the US may have a flawed democracy with elements of oligarchy.Received 9thDecember 2020; Revised 2nd March 2021; Accepted 20th March 2021